2022
DOI: 10.3389/fnhum.2021.787157
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Movements via Motor Gamma Oscillations

Abstract: The ability to perform movements is vital for our daily life. Our actions are embedded in a complex environment where we need to deal efficiently in the face of unforeseen events. Neural oscillations play an important role in basic sensorimotor processes related to the execution and preparation of movements. In this review, I will describe the state of the art regarding the role of motor gamma oscillations in the control of movements. Experimental evidence from electrophysiological studies has shown that motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 154 publications
(233 reference statements)
2
13
0
Order By: Relevance
“…Another study of a bimanual finger tapping task involving congruent and incongruent cued trials showed that MRGS was reduced with increased contextual response certainty (Wiesman et al, 2021 ). Although it is not clear exactly what the change in gamma power reflects in the current study, it lends further support to prior arguments that MRGS reflects higher‐level motor control or cognitive processing during movement in response to dynamic environmental demands (Nowak et al, 2018 ; Ulloa, 2022 ). While the current study did not reveal changes in FMT power over trials, prior work suggests that FMT and gamma oscillations may work together for motor learning by underpinning network‐level plastic changes (Nowak et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Another study of a bimanual finger tapping task involving congruent and incongruent cued trials showed that MRGS was reduced with increased contextual response certainty (Wiesman et al, 2021 ). Although it is not clear exactly what the change in gamma power reflects in the current study, it lends further support to prior arguments that MRGS reflects higher‐level motor control or cognitive processing during movement in response to dynamic environmental demands (Nowak et al, 2018 ; Ulloa, 2022 ). While the current study did not reveal changes in FMT power over trials, prior work suggests that FMT and gamma oscillations may work together for motor learning by underpinning network‐level plastic changes (Nowak et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
“…Advances in MEG analytical methods, such as differential beamforming, have optimized the spatial and spectral resolution of MEG and its use to investigate the spatial organization of neural oscillatory dynamics over the motor cortex (Barratt et al, 2018 ; Cheyne et al, 2006 ; Cheyne et al, 2008 ). These methodological developments have resulted in significant advances in knowledge regarding the association between movement‐related cortical oscillations (in the beta band, 14–30 Hz, and gamma band, 60–90 Hz) and motor behavior during development, in health and in disease (Gaetz et al, 2010 , 2013 , 2020 ; Heinrichs‐Graham et al, 2014 ; Heinrichs‐Graham & Wilson, 2015 , 2016 ; Muthukumaraswamy, 2010 ; Ulloa, 2022 ; Wilson et al, 2010 ; Wilson et al, 2011 ).…”
Section: Background and Significancementioning
confidence: 99%
“…Gamma coupling dynamics scale with increased muscle contraction and coordination ( 14 , 38 ), and may facilitate a similar increased muscle recruiting role during reactive balance stepping. The cortical gamma rhythm covers a wide frequency range and although we analyzed two distinct frequency bands, cortical coupling in either band occurred mostly between foot off and foot strike.…”
Section: Discussionmentioning
confidence: 99%
“…The cortical gamma rhythm covers a wide frequency range and although we analyzed two distinct frequency bands, cortical coupling in either band occurred mostly between foot off and foot strike. Therefore, we will discuss these results as general gamma dynamics [for an extensive review on gamma oscillations and CMC during the control of movements see Ulloa ( 38 )]. Interestingly, we observed gamma rather than beta coupling throughout the reactive step response.…”
Section: Discussionmentioning
confidence: 99%
“…Vicente et al ( 2022 ) noted that increased gamma power and long-range gamma synchronization have been identified in conscious perception; but they have also been found across the neocortex in association with a wide variety of brain circumstances (Muthukumaraswamy, 2013 ) ranging from ongoing tonic pain (Schulz et al, 2015 ) to preparation for and execution of movements (Ulloa, 2022 ). Vicente et al discerningly listed several reasons not to place too much importance on this one patient's EEG: the patient's traumatic brain injury and subdural hematoma, the anesthesia-induced loss of consciousness, the dissociative drugs given to the patient, the anticonvulsant drugs to control his seizures, and the patient's asphyxia and hypercapnia.…”
Section: Source Of Gamma Oscillationsmentioning
confidence: 99%